Inconspicuous Ecocide: Photographs of Environmental Damage Wrought by the Russian Invasion of Ukraine - Denis Skopin (Kronos)
This article is devoted to the problem of photographic representation of the environmental harm caused by the Russian invasion of Ukraine. In many cases, this damage is intentional and due to the military strategy employed by the Russian military. The most illustrative case of this kind is the destruction of the Kakhovka hydroelectric dam, whose consequences are comparable with those of the Chernobyl catastrophe, and which are often referred to as 'ecocide'. In this article, I clarify the concept of 'ecocide', which is vague, contested and not yet considered a crime by the international criminal court. I interpret this concept in a biopolitical perspective, as a form of domination over the biological in the broad sense of the word (over biosphere). I also examine photographs of environmental damage caused by the Russian invasion, in particular, the photographs showing the destruction of the Kakhovka dam and its consequences. The aim of my analysis is to find out what kind of visual records might visualise the ecocide and if the existing photographs from Kakhovka meet our expectations. This discussion refers to earlier debates about 'genocide photographs' and environmental photography. I argue that photographic records from Kakhovka, which are inconspicuous in visual terms despite the clearly ecocidal nature of the disaster, are nevertheless valuable and teach us an important lesson: we should not expect exhaustive photographs of ecocide, which can rather be represented, with a certain degree of approximation, through an evolving body of always imperfect and lacunar images.